HIV infection and sexual partnerships and behaviour among adolescent girls in Nairobi, Kenya - Rositch, AF (2012)
Early sexual partnerships place young women in sub-Saharan Africa at high risk for HIV. Few studies have examined both individual- and partnership-level characteristics of sexual relationships among adolescent girls. A cross-sectional survey of sexual history and partnerships was conducted among 761 adolescent girls aged 15–19 years in Nairobi, Kenya. Rapid HIV testing was conducted and correlates of HIV infection were determined using multivariate logistic regression. The HIV prevalence was 7% and seropositive adolescents had a younger age at sexual debut (P < 0.01), more sexual partners in 12 months (P = 0.03), and were more likely to report transactional or non-consensual sex (P < 0.01). Girls who reported not knowing their partner’s HIV status were 14 times as likely to be HIV-seropositive than girls who knew their partner’s status (adjusted odds ratio: 14.2 [1.8, 109.3]). Public health messages to promote HIV testing and disclosure within partnerships could reduce sexual risk behaviours and HIV transmission among adolescents.